Handbook on community profiling for people-oriented forestry. - Philippines. Department of Environment and Natural Resources. Upland Development Working Group. Community Profiling Committee; Philippines. Department of Environment and Natural Resources. Upland Development Program (Quezon City Upland Development Program, DENR, 1991)
"Provides a methodology for incorporating information gathering into the processes of site and project selection as well as initial planning for project implementation." Designed for use by development workers involved in the people-oriented forestry programs of the DENR. It includes Community Profiling, Preparations and Secondary Data Gathering, Primary Data Gathering, Report Writing and Sample Profile.
Keywords: Social forestry programs -- Data processing -- Philippines -- Handbooks, manuals, etc; Forestry projects -- Data processing -- Philippines -- Handbooks, manuals, etc